The role of modern architecture and interior design in the Latvian brending - Irbīte, Andra (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
The national identity or the originality of expression of a nation`s culture is an important factor that is confining identification of a numerically and geographically small country in the age of globalization, with an inestimable role in the nation's self-maintenance. The respect for cultural heritage and valuable contemporary architecture and interior design have invaluable importance in forming national identity. The main issues of Architecture and design about the functional and aesthetic, form and materials, arrangement and integrity have always been and currently are important. Each successive step is the continuation of previous experience. Then the language of Architecture and interior design semantics, which is the visible consequence of certain functions, exposed in a spatial form, is revealed both in the structural level and in the overall environmental quality of the conceptual context – global semantic level. Latvian contemporary architecture and interior design are not considered in isolation from the processes in the world, so the purpose of this research is to identify and analyze the examples characterized by the spatial quality as well as the objects that claim to have a semantic message:the state culture signs, with the assumption, that the cultural tourism in Latvia could be entertaining both for people who live in Latvia and for guests of the country. Analysis of selected examples demonstrates that in both urban and rural areas in Latvia are buildings, their interiors and arranged environment, that might be interesting for travelers.